Leveraging dynamic capabilities for green transformation: A strategic path to sustainable supply chain performance in the Nigerian cement industry - Remi-Aworemi , Favour Iretomiwa; Salami, Akeem Olanrewaju (UIR Press, 2026)
Purpose: This study examines the whether the dimensions of the Dynamic Capabilities View (DCV), sensing, seizing, and reconfiguring capabilities, directly predict sustainable supply chain performance (SSCP) in the Nigerian Cement industrial. Design/methodology/approach: The quantitative cross-sectional survey of 385 employees across Dangote Cement Plc., Lafarge Africa Plc., and BUA Cement Plc. was analysed through structural equation modelling (SEM) implemented in IBM SPSS AMOS version 23. A two-stage analytical procedure encompassing confirmatory factor analysis (CFA) for measurement model evaluation and structural path estimation was adopted. Bias-corrected bootstrap confidence intervals from 5,000 resamples were used to verify the robustness of all structural paths. Findings: The result demonstrated excellent psychometric properties and outstanding fit. All the three capability dimensions exerted significant positive direct effects on SSCP: sensing capability was the strongest predictor, followed by seizing capability and reconfiguring capability. Bootstrap confidence intervals confirmed the reliability of all three structural paths. Limitations and Research implications: The cross-sectional, single-industry design limits causal inference and generalisability. Longitudinal designs incorporating objective emissions and efficiency data across multiple sectors are warranted. Practical Implications: Nigerian cement industry should build formal environmental intelligence systems, invest deliberately in green technology, and restructure supply chain governance to institutionalise sustainability. Policymakers should complement regulatory enforcement with capacity-building support and green financing instruments aligned with Sustainable Development Goal 9. Originality/value: This study provides the first SEM-based empirical test of all three DCV micro-foundations as independent direct predictors of SSCP in Sub-Saharan Africa, contributing both theoretical extension and actionable guidance for an underrepresented industrial context.